Variation in the Level and Dynamics of Unemployment by Poviats in Poland - Kwiatkowski, Eugeniusz; Kwiatkowska, Emilia (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2020)
Objective: The paper discusses the variation in unemployment in Polish poviats in 2011–2019 by rate and dynamics of unemployment. It identifies the most difficult and leading poviat labour markets and the most important economic factors determining the classification of poviats in terms of the unemployment rate and the flows between employment and unemployment. Research Design & Methods: Poviat labour markets were classified based on the mean and standard deviation and econometric analyses using logit models of binominal variables. Findings: Significant variation in the level and dynamics of unemployment in the Polish poviats in the years 2011–2019 was confirmed. Poviats with a favourable labour market situation are located in western Poland while those facing greater challenges are located in the east. The highest variation between poviat labour markets occurs in Mazowieckie voivodeship. Three economic determinants increase the chances of a poviat being included in the low unemployment rate group and at least with moderate levels of labour flows. They are: high levels of fixed assets, high industrial output and a high level of entrepreneurship. Implications / Recommendations: In the years 2011–2019, average unemployment rates decreased while labour flows between employment and unemployment increased somewhat. However, these processes have not significantly changed the grouping of the poviat labour markets. Significant variation in the level and dynamics of unemployment in the Polish poviats continues. The estimations of the model indicate the spatial structure of economic stimulants will determine differences between local labour markets with respect to the unemployment level and dynamics. Contribution: The article shows the variation of unemployment in the Polish poviats results both from the variation of unemployment rates and variation in the dynamics of labour flows between unemployment and employment. Unemployment variation in the poviats was described for two stages of the business cycle and the most important factors determining the level and dynamics of unemployment in the poviats were identified.